2018
DOI: 10.1080/14767058.2018.1450382
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent shoulder dystocia: are we any closer to prediction?

Abstract: Recurrent shoulder dystocia is an unpredictable obstetric complication with potentially devastating consequences. Individual assessment and thorough counselling should be offered to women contemplating a subsequent planned vaginal birth with specific attention paid to those women where the estimated birthweight is >4000 g or greater than in the index pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
18
1
Order By: Relevance
“…Despite the highly unpredictable nature of shoulder dystocia, because of the severity of injury it is one of the most litigated complications of childbirth in the United States. 3,5 The risk of legal liability in the United States when caring for women and newborns has increased over the past 20 years. 8 It is reported that 15% of certified nurse-midwives and certified midwives (CNMs/CMs) and 91% of obstetriciangynecologists have been named in lawsuits.…”
Section: Legal Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the highly unpredictable nature of shoulder dystocia, because of the severity of injury it is one of the most litigated complications of childbirth in the United States. 3,5 The risk of legal liability in the United States when caring for women and newborns has increased over the past 20 years. 8 It is reported that 15% of certified nurse-midwives and certified midwives (CNMs/CMs) and 91% of obstetriciangynecologists have been named in lawsuits.…”
Section: Legal Implicationsmentioning
confidence: 99%
“…22 There is limited research regarding these effects, and more study is needed to quantify the magnitude of this problem. 3,8,31 Clinicians may experience a condition called secondary traumatic stress that is similar to PTSD. Secondary traumatic stress occurs as a result of the emotional distress that arises from the desire to help someone who is traumatized or suffering.…”
Section: Psychological Impactmentioning
confidence: 99%
See 3 more Smart Citations